Antiferromagnetic single-layer spin-orbit torque oscillators - Stamenov, Plamen; Rode, Karsten; Coey, John (My University, 2019)
We show how a charge current through a single antiferromagnetic layer can excite and control self-oscillations. Sustained oscillations with tunable amplitudes and frequencies are possible in a variety of geometries using certain classes of noncentrosymmetric materials that exhibit finite dissipative spin-orbit torque. We compute the steady-state phase diagram as a function of the current and spin-orbit torque magnitude. The anisotropic magnetoresistance causes the conversion of the resulting AF oscillations to a terahertz AC output voltage. These findings provide an attractive and novel route to design terahertz antiferromagnetic spin-orbit torque oscillators in simple single-layer structures.
PUBLISHED
Keywords: Spin dynamics; Spin-orbit coupling; Spintronics; Antiferromagnets; Nanoscience & Materials; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics